Spread of the blaOXA-23-containing Tn2008 in carbapenem-resistant Acinetobacter baumannii isolates grouped in CC92 from China - Chen, Yisheng; Gao, Jing; Zhang, Haomin; Ying, Chunmei (Frontiers in Microbiology, 2017)
The rapid expansion of carbapenem-resistant Acinetobacter baumannii (CRAB) clinical isolates is a big issue. We investigated the antibiotic susceptibility, molecular epidemiology and resistance gene of A. baumannii collected at two hospitals in Shanghai, China. Besides, the A. baumannii PCR-based replicon typing method (AB-PBRT) was conducted to categorize the plasmids into homogeneous groups on the basis of replicase genes. Most CRAB isolates showed high-level resistance to almost all antibiotics but retain susceptibility to colistin and tigecycline. A total of 101 isolates carried blaOXA-51-like gene. Sequencing identified the presence of blaOXA-66 for CRAB isolates. blaOXA–23 gene were discovered in all CRAB isolates. Each CRAB isolate contained 1–3 of 19 different plasmid replicase (rep) gene homology groups (GRs) and the GR6 (repAci6) was ubiquitous. Genotyping by Multilocus Sequence Typing (MLST) showed seven defined MLST patterns and three novel STs were found. eBURST analysis indicated they were all grouped in CC92 (GCII) with the most frequent ST208 (50%). Two blaOXA–23-bearing transposons were found: Tn2006 and Tn2008. Tn2008 were detected in 54 (96.4%) isolates and Tn2006 in two remaining isolates. The blaOXA–23 carbapenem gene was vitally associated with repAci6 plasmid belong to CC92 clonal group. Our survey revealed severe drug resistance in A. baumannii isolates. Tn2008-containing CC92 A. baumannii were endemic, which may facilitate the blaoxa23 dissemination.